Conjugates of Recombinant Protein‐Based Polymers: Combining Precision with Chemical Diversity. Issue 6 (23rd March 2022) - Hadar, Dagan; Strugach, Daniela S.; Amiram, Miriam
Abstract : Inspired by nature, scientists have harnessed the natural protein translation machinery to produce intricate and precise protein‐based polymers (PBPs)—composed of natural amino acid monomers and assembled on the nano‐to‐macro scale—for drug and gene delivery, to sense the environment, to produce valuable molecules, and to grow cells and tissues. Beyond the chemical repertoire of natural amino acids, the conjugation of chemically diverse molecules to recombinant PBPs can increase the ability of the latter to mimic or modify the remarkable properties of natural biomaterials and to impart new functions. In this review, recent progress in the production and application of recombinant PBP‐conjugates is described. First, the various approaches for protein conjugation or crosslinking are briefly discussed and then the utility of this approach for imparting new or improved properties and functions onto PBPs composed of elastin‐, resilin‐, silk‐, or collagen‐based sequences is demonstrated. Finally, emerging knowledge of and technologies for PBP‐conjugate production with the potential to expand the use of such precise and chemically diverse polymers in biomedicine is discussed. Abstract : Protein‐based polymers (PBPs) are composed of natural amino acids and can be recombinantly produced with exquisite precision by using the protein translation machinery. This review describes recent progress in the production of PBP conjugates, in which chemically diverse molecules are conjugated to the PBPs to either improve or impart new properties and functions.